2021
DOI: 10.1108/ecam-04-2021-0295
|View full text |Cite
|
Sign up to set email alerts
|

Integrating road information modeling (RIM) and geographic information system (GIS) for effective utility relocations in infrastructure projects

Abstract: PurposeTransportation infrastructure projects are inevitably delayed due to delays in the completion of underground utility relocation. Unfamiliar location, difficulty in utility identification and use of ineffective coordination practices hamper timely completion of utility relocation works. This paper aims to develop integrated road information modeling (RIM) and geographic information system (GIS) models to assist early identification of utilities and effective coordination during utility relocation in infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…FGD is an exploratory discussion technique that has been extensively used in research studies to collect expert opinions [47], [61] and is particularly convenient for exploring the diverse perspectives of participants with similar backgrounds, opinions, or experiences on a research topic [62], [63]. Gold and Vassell [61] highlighted the advantages of focus groups such as time-effective and cost-effective.…”
Section: Focus Group Discussion (Fgd)mentioning
confidence: 99%
See 1 more Smart Citation
“…FGD is an exploratory discussion technique that has been extensively used in research studies to collect expert opinions [47], [61] and is particularly convenient for exploring the diverse perspectives of participants with similar backgrounds, opinions, or experiences on a research topic [62], [63]. Gold and Vassell [61] highlighted the advantages of focus groups such as time-effective and cost-effective.…”
Section: Focus Group Discussion (Fgd)mentioning
confidence: 99%
“…Gold and Vassell [61] highlighted the advantages of focus groups such as time-effective and cost-effective. They can also generate satisfactory output with the involvement of 5 to 10 participants [62]. Yu and Leung [64] addressed that 4 to 6 participants constituted mini focus groups and 7 to 10 participants constituted small focus groups.…”
Section: Focus Group Discussion (Fgd)mentioning
confidence: 99%
“…Studies in the field of transportation infrastructure have shown that implementing GIS in a project could reduce project costs while increasing workflow accuracy and efficiency [37,134,135]. GIS capabilities were employed to find highway sections that received multiple reconstructions over their planning prospect [136], apply geotechnical considerations in a highway layout [102], detect utility conflicts in railway projects prior to construction [38], prioritize maintenance plans [137], create a geo-enabled geometric design for highways, conduct environmental assessment of concrete mixes [138], and optimize construction site material distribution layout [139]. Studies also employed GIS for pavement performance analysis to investigate the impact of different factors such as precipitation, [140][141][142], mass movement susceptibility prediction [143], sustainability-based management [144], construction quality evaluation [27], functional road classification [145], and climate change risk assessment of critical infrastructure [146].…”
Section: Geospatial Analysis Tools For Project Planning (Geospatial A...mentioning
confidence: 99%
“…Sharafat et al, (2021) developed a BIM-GIS-based integrated framework for an underground utility management system for earthwork operations. Likewise, Rajadurai and Vilventhan (2021) developed an integrated model using Road Information Modelling (RIM) and GIS to facilitate an ongoing utility relocation in infrastructure projects. However, all existing systems and frameworks developed are based on different model standards and experience loss of information during conversion.…”
Section: Recommendation For Future Research On Gis Application In The...mentioning
confidence: 99%